ENDOPROSTHESIS OF THE SHOULDER JOINT IN METASTATIC LESIONS OF THE PROXIMAL HUMERUS DURING IMMUNOSUPPRESSIVE THERAPY - M. V. Ivanova; V. Yu. Karpenko; A. V. Bukharov; V. A. Derzhavin (Исследования и практика в медицине, 2017)
The incidence of primary malignant tumors of the skeleton is an average of 1.5 for men, for women – 0.9 per 100 000 population. Morphologically most common are: osteosarcoma (55-63%), chondrosarcoma (17–25%) and Ewing’s sarcoma family of tumors (8–15%). Metastatic lesions of long bones occurs 2-4 times more common than primary tumors and often are diagnosed with breast cancer in 65–73%, of prostate cancer in 56–68% and lung cancer in 30–36% of patients. World Data standard treatment for patients is a combined approach, one of the stages is a surgical treatment. In modern oncoorthopedics the standard of surgical treatment of patients with tumor lesions of bone is the conduction of segmental bone resection and oncological arthroplasty. However, just as with other surgical interventions, in arthroplasty with large joints that is associated with the introduction of foreign material into the body, there are complications which usually are infectious by nature. Complications associated with the continuous use of immunosuppressive therapy include bacterial and viral infections. It must be emphasized that in the context of immunosuppression bacterial infection is much greater and is accompanied by greater mortality than in patients without immunosuppression. The frequency of complications in patients who undergo total joint replacement after organ transplantation can be significantly reduced by the correction of metabolic disorders, the purpose of broad-spectrum antibiotics in the perioperative period and careful rehabilitation. It is necessary to work closely with the transplantologists. Also the method of using a local antibiotic administered directly to the site of surgery can be used. This method has significant advantages because of the high local concentrations with minimal risk of systemic toxicity. In this paper we present a clinical case of performing resection of the proximal humerus to the shoulder joint arthroplasty in patient on immunosuppressive therapy.